Antioxidant Activity of Combination Simplicia and Extract of Avocado Peel (Persea americana Mill.) and Lime Peel (Citrus aurantifolia) - Rahayuningrum, Elsa Dwi; Zamruddin, Nur Masyithah; Prasetya, Fajar (Journal of Tropical Pharmacy and Chemistry, 2024)
The avocado peel (Persea americana Mill.) and lime peel (Citrus aurantifolia) are biodegradable waste materials that contain antioxidant activities. This study aims to determine the antioxidant activities of avocado peel and lime peel extracts on their single and combined form. Samples were extracted with the maceration method using 96% ethanol solvent, then an antioxidant activity test towards DPPH (2,2-diphenyl-1-picrylhydrazyl) radical inhibition measured using the UV-Vis spectrophotometer. This research showed that the antioxidant activities obtained with the value of IC50 (inhibition concentration) are at 24.82 ppm from the avocado peel extract, 131.12 ppm from lime peel extract, and also from the simplicia combination with the ratio of 1:1; 1:2; and 2:1 are respectively at 45.01 ppm, 87.41 ppm; and 38.49 ppm, meanwhile on the combined extracts with the ratio of 1:1; 1:2; and 2:1 are respectively at 31.16 ppm; 39.28 ppm; and 11.69 ppm and followed by ascorbic acid at 4.35 ppm.